2009
DOI: 10.1016/j.comppsych.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-criticism versus neuroticism in predicting depression and psychosocial impairment for 4 years in a clinical sample

Abstract: The present study extended previous findings demonstrating self-criticism, assessed by the Dysfunctional Attitude Scale (DAS) (Weissman AN, Beck AT. Development and validation of the Dysfunctional Attitude Scale: a preliminary investigation. Paper presented at the 86th Annual Convention of the American Psychological Association, Toronto, Ontario, Canada, 1978), as a potentially important prospective predictor of depressive symptoms and psychosocial functional impairment over time. Using data from a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 63 publications
(133 reference statements)
6
58
0
2
Order By: Relevance
“…Non-judgment also showed to significantly predict psychological symptoms. These two facets measure a self-critical attitude that has shown to be an important determinant for depressive symptoms (Dunkley et al 2006 2009). Finally, our findings suggest that the mindfulness skills to be observing, able to describe internal and external experiences, non-reacting to emotions and thoughts, and to act with awareness, are all predictors of positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…Non-judgment also showed to significantly predict psychological symptoms. These two facets measure a self-critical attitude that has shown to be an important determinant for depressive symptoms (Dunkley et al 2006 2009). Finally, our findings suggest that the mindfulness skills to be observing, able to describe internal and external experiences, non-reacting to emotions and thoughts, and to act with awareness, are all predictors of positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that SC can be distinguished from neuroticism, as SC uniquely relates to negative interpersonal characteristics (e.g., negative social interactions) and depressive symptoms (e.g., Dunkley, Sanislow, et al, 2006;Dunkley, Sanislow, Grilo & McGlashan, 2009; see Zuroff et al, 2004). There is also some evidence that SC perfectionists' higher reactivity to stress is due to overlap with both PS and neuroticism in nonclinical community adults (Dunkley, Mandel, et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…The relation between SC perfectionism and depressive symptoms was partially mediated by lower perceived social support in a study of undergraduate students (Sherry, Law, Hewitt, Flett, & Besser, 2008). Further, a test of a 3-wave mediational model in a sample of patients demonstrated that negative perceptions of social support at 3 years mediated the relation between Time 1 SC perfectionism and depression over 4 years (Dunkley et al, 2009). …”
Section: Lower Perceived Social Support As a Mediatormentioning
confidence: 94%